1998
DOI: 10.1073/pnas.95.19.11257
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of LMO 4 , an LMO gene with a novel pattern of expression during embryogenesis

Abstract: LMO4 is a novel member of the LIM-only (LMO) subfamily of LIM domain-containing transcription factors. LMO1, LMO2, and LMO4 have distinct expression patterns in adult tissue, and we demonstrate that nuclear retention of LMO proteins is enhanced by the nuclear LIM interactor (NLI). In situ hybridization to early mouse embryos of 8-14.5 days revealed a complex pattern of LMO4 expression spatially overlapping with NLI and LHX genes. LMO4 expression in somite is repressed in mice mutant for the segment polarity ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
98
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(110 citation statements)
references
References 35 publications
(34 reference statements)
12
98
0
Order By: Relevance
“…Of the set of 17 LIM genes comprising Lhx1-9, Lmx1a, 1b, Isl1, 2, and Lmo1-4, we focused on only those genes for which our preliminary studies or published reports from other groups showed expression in the dorsal telencephalon (Boehm et al, 1991;Foroni et al, 1992;Fujii et al, 1994;Porter et al, 1997;Sheng et al, 1997;Kenny et al, 1998;Bertuzzi et al, 1999;Retaux et al, 1999;Millonig et al, 2000). Lhx3,4,6,7,8,Lmx1b, and Isl1, 2 were excluded because previously reported expression patterns reveal their expression to be in only ventral but not dorsal telencephalon, or restricted to nontelencephalic CNS regions, in addition to non-CNS structures (Thor et al, 1991;Li et al, 1994;Tsuchida et al, 1994;Zhadanov et al, 1995;Yamashita et al, 1997;Chen et al, 1998;Grigoriou et al, 1998;Kitanaka et al, 1998).…”
Section: Resultsmentioning
confidence: 99%
“…Of the set of 17 LIM genes comprising Lhx1-9, Lmx1a, 1b, Isl1, 2, and Lmo1-4, we focused on only those genes for which our preliminary studies or published reports from other groups showed expression in the dorsal telencephalon (Boehm et al, 1991;Foroni et al, 1992;Fujii et al, 1994;Porter et al, 1997;Sheng et al, 1997;Kenny et al, 1998;Bertuzzi et al, 1999;Retaux et al, 1999;Millonig et al, 2000). Lhx3,4,6,7,8,Lmx1b, and Isl1, 2 were excluded because previously reported expression patterns reveal their expression to be in only ventral but not dorsal telencephalon, or restricted to nontelencephalic CNS regions, in addition to non-CNS structures (Thor et al, 1991;Li et al, 1994;Tsuchida et al, 1994;Zhadanov et al, 1995;Yamashita et al, 1997;Chen et al, 1998;Grigoriou et al, 1998;Kitanaka et al, 1998).…”
Section: Resultsmentioning
confidence: 99%
“…LMO4 and LDB1 are ubiquitously expressed in the mouse embryos, including epithelial and mesenchymal areas, when compared to the exclusive expression of other LMO family members and LDB2 in neuronal and haematopoietic cells (Visvader et al, 1997;Kenny et al, 1998;Sugihara et al, 1998;Toyama et al, 1998;Hermanson et al, 1999;Thaler et al, 2002). The LIM domain of LDBs contributes to the binding of transcription factors, including LIM-homeodomain, zinc-finger and basic helixloop -helix (bHLH) proteins (Agulnick et al, 1996;Jurata et al, 1996;Bach et al, 1997;Morcillo et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…The most recently identified member, LMO4, shares only 50% homology with the LIM domains of other LMO proteins. The LMO4 gene is widely distributed in embryonic tissues (Kenny et al, 1998;Sugihara et al, 1998), and involved in negative regulation of breast carcinoma cell differentiation (Visvader et al, 2001). LMO4 binds with a high affinity to the LIM domain-binding proteins, LDB1 (CLIM2, NLI1) and LDB2 (CLIM1) (Agulnick et al, 1996;Jurata et al, 1996;Sugihara et al, 1998).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Examination of the protein sequence revealed that this cDNA clone corresponded to a mRNA encoding a new member of the LIM-only LMO family of proteins. A similar cDNA has recently been described (Kenny et al, 1998) and the sequence of the human counterpart (which is identical in translated product with the mouse sequence reported here) was previously deposited in the Genbank database by J Racevskis, A Dill and H Ruan (Accession number: U24576). In keeping with other members of the LMO family, this new member is designated Lmo4.…”
mentioning
confidence: 93%